PERGESERAN PERAN MAMAK TERHADAP KEMENAKAN DALAM ADAT MINANGKABAU DI KANAGARIAN SIMALANGGANG (Kecamatan Payakumbuh Kabupaten 50 Kota) - Marisa Anjela; M. Razif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Shifting the roie of mamak occurring in Kanagarian Simalanggang constituting asocial phenomena that happened in the society in Kanagarian Simalanggang has an importantposition, mamak is the figure of a leader for the families especially the nephew of mamak it,mamak in custom of Minangkabau have broad enough role which was in educating nephew,in terms of property inheritance and in terms of marriage nephew her, but in fact the thismoment, with the rapid advancement of development period, the role of mamak inKanagarian Simalanggang experiencing shift. Mamak at the moment now is no longernoticing nephew her as is done by mamak-mamak formerly according to rule the custom. Thepurpose of this research which is to find out froms changes the role of mamak in KanagarianSimalanggang and to know anything factors a causing shifting mamak role against thenephew in Kanagarian Simalanggang. Data analysis conducted by ways of quantitatifdescriptive. Data capture techniques in this researcher searching from one respondent torespondent another, so the number of sampel to be much, the author took 10 respondent ofthe four jorong who number of a whole samples there are 40 people with the tribe of beingdiverse. From the research can be concluded that the role of mamak in KanagarianSimalanggang experiencing change, this can be seen clearly that the mamak most of nolonger execute his role in accordance with the provision custom. This research also revealedof factors causing shift the role of mamak against nephew in Kanagarian Simalanggang thatis a factor of education, religion, economy, strengthening the role of the nuclear family, lackof socialization, and the absence of sanctions.Keywords : mamak, role, mutation